Axial Spondyloarthritis in Black Americans: An Observational Study From Five Centers in Shelby County, Tennessee - Krishna Kommineni; Iman Abutineh; Cathy Chapman; Debendra Pattanaik; Mohamad Bittar (ACR Open Rheumatology)
Objective Axial spondyloarthritis (axSpA) is an immune‐mediated disease that predominantly affects the axial skeleton. The objective of this study was to describe the frequency and clinical characteristics of axSpA in Black Americans in Shelby County. We also aimed to report diagnostic delays, disease severity, and health disparities in this population. Methods This was a retrospective observational study in which electronic records of patients with axSpA were reviewed across five centers in Shelby County. Patients were identified using International Classification of Diseases codes. Data on demographics, clinical characteristics, and imaging were collected. The frequency was reported. Two‐group comparisons were done using the chi‐square test and two‐sample t‐test. Multivariable logistic and linear regression methods were used to compare sacroiliitis grades and delay in diagnosis, respectively, after adjusting for confounders. Results Black Americans constituted 32% (n = 78) of the 244 patients with axSpA identified. Black Americans had significantly more hip involvement, more elevations in C‐reactive protein, less HLA–B27 positivity, and less family history positivity when compared with White patients. After adjusting for age, sex, and HLA–B27, Black Americans had twice as higher odds of having advanced grades of sacroiliitis on x‐rays compared to White Americans (odds ratio 2.32 [95% confidence interval 1.23–4.44]). AxSpA was associated with significant diagnostic delays in both races. Conclusion A significant proportion of patients with axSpA in Shelby County were Black Americans. The study identified that Black Americans have more odds of having advanced sacroiliitis on x‐rays, more hip involvement, and higher markers of inflammation. It also showed that, regardless of race or ethnicity, there is a significant diagnostic delay.